Risk management system in Russian design organizations: rationale for implementation - A. O. Postolakiy; A. V. Savin (Вестник университета, 2021)
The article discusses the specific features of risk management in Russian design organizations. The advantages of implementing a risk management system in such structures in the short and long term have been shown. A review of the methodological base of project risk management, formed by the efforts of Russian and foreign scientists, has been performed. The article presents typical problem situations caused by the implementation of risks inherent in design organizations that threaten its stable operation. The key reasons for the formation of risk factors have been considered. The negative consequences of passive risk management have been diagnosed. Prerequisites for the deployment of a risk management system in design organizations have been presented. The stages of implementation of the risk management system have been described. It has been concluded about the effectiveness and efficiency of the risk management system in the design organization.